Hegemonic dialectics between power and resistance in the Indonesian sharing economy: Study of Gojek - Irsanti Widuri Asih; Heru Nugroho; Budiawan Budiawan (Informasi, 2022)
Gojek is an Indonesian platform-based on-demand ride-hailing business that has attracted some researchers to conduct studies in this newly emerged economy field through various approaches. Most researchers see the phenomenon of Gojek as part of the global disruptive technology movement that positively impacts the Indonesian economic and socio-cultural aspects of society. Some others expose the asymmetrical relationship between the platform and its driverpartners. No study analyzed it from the perspective of a dialectical hegemony that transpires between the platform and its driver-partners. Using a qualitative method, this article will fill in the gaps in the study of the Gojek phenomenon from the Gramscian Theory of Hegemony perspective to uncover the dialectical relationship between the digital platform and its driver-partners. The platform articulates hegemony actions through gamification and algorithm system, the concept of work, the internalization of corporate values, the Award Programs, the Kopi Darat Program, the driver-partners communities, Gojek’s Task Force and the driver-partners influencers. The driver-partners perform resistance by conducting demonstrations and boycotts, using various application modifications, and serving over one platform.